Outlining the Potential Role of Humic Products in Modifying Biological Properties of the Soil—A Review - Pukalchik, Maria; Kydralieva, Kamila; Yakimenko, Olga; Fedoseeva, Elena; Terekhova, Vera (Frontiers in Environmental Science, 2019)
There is a growing awareness among farmers about the importance of soil for sustaining crop production and soil health. Marked interests in “environmentally-friendly” soil fertilization in agriculture has attracted significant attention in the last decades. A wide range of commercial humic products (HPs) are used as soil supplements to improve the nutrient utilization efficiency of plants as well as to increase crop production. However, the implications of increased HPs use for soil biology are being questioned, but a comprehensive review on this topic is lacking. The aims of this review are to understand behavior of HPs applied to soil, with a special focus on environmental protection issues, and to summarize the available data how HPs may influence the soil microbial communities, including fungi and bacteria strains. The interaction between HPs and soil inhabitants is highly complex and is controversial to a certain extent for several reasons. First, applying HPs may promote specific bacteria communities (Acidobacteria, Actinobacteria, Bacteriodeites, etc.) rather than other microbiome species. Soil enzymes such as laccase, peroxidase and dehydrogenase were seemingly affected as well. Applying HPs may result in the microbial respiration of CH4, preventing the production of CO2 from microbial respiration. These results would potentially lead to an overall decrease in the microbial respiration of CH4, which is associated with a deficit in CO2. Furthermore, HPs can control the nematode population in different soils. Finally, applying HPs in terms of physiological functioning can also have various consequences for different groups of soil fungi. However, the conditions that promote specific effects (chemical composition of HPs, environmental conditions, etc.) have yet to be investigated. Given the surveyed data, we conclude that there are gaps in the current knowledge of this topic. We propose an integrated approach including a targeted research involving not only species of plants but also the integrated chemical, toxicological and biological analyses as a useful approach of soil health protection.